A Decision-Making Model for the Transportation of Municipal Solid Wastes - Fatih Kamaoğlu; Nesli Aydın (Doğal Afetler ve Çevre Dergisi)
The management of waste with minimum cost and the environmental burden has recently gained importance in the circular economy. In this study, alternatives for the transportation of wastes by rail and road were compared in terms of cost, environment and personnel requirement benchmarks by using the multi-criteria decision-making software - Right Choice (2.0). The transportation of waste by road is shown with Alternative 1, while the transportation by rail is represented by Alternative 2 (by loading waste-carrying trucks and trailers on the train), Alternative 3 (by loading only trailers on the train) and Alternative 4 (by loading only wastes on the train). As a result, it was determined that the optimum option to transfer the wastes is as specified in Alternative 4, to load only the wastes on the wagons. Importantly, the low operation-maintenance cost of Alternative 4, in other words, its high performance on this benchmark and the high relative importance of the operation-maintenance cost attributed by the stakeholders play a vital role. According to the sensitivity analysis results, Alternative 3 appears as another option close to Alternative 4 while Alternatives 1 and 2, however, remain as options to be evaluated where Alternatives 3 and 4 are not included in decision-making at all. The results of this study show that, depending on the scoring of the criteria in the decision tree, Alternative 4 or 3 could be a better option than the other alternatives, by reducing the number of alternatives and highlighting the good performers.